'Peace-building as state-building'? Rethinking liberal interventionism in contexts of emerging states. Issue 6 (2nd November 2017) - Balthasar, Dominik
Abstract: Contemporary policy-making guided by the 'liberal peace' holds that peace is necessary for states to emerge, and that peace-building and state-building do not only go in tandem, but are mutually reinforcing. Yet, in view of both the historical record of state-making and empirical evidence provided by liberal interventionism, this proposition appears questionable. While scholars have shown that state-making has, historically, been as much associated with war than with peace, cases from Afghanistan to Somalia suggest that state-making is inherently conflictive, frequently upsetting nascent peace. In order to shed light on the reasons underpinning the relationship between prevailing peace-building practices and the fundamental exigencies of state-making, this article pursues a theoretical argument. It proposes that while peace-building is principally about creating a situation of non-violent co-existence despite prevailing differences and, thus, essentially geared at accepting and enshrining institutional and identity pluralism, state-making is vitally aimed at replacing institutional and identity multiplicity with greater degrees of rule hegemony and standardisation. Applying the prism of 'rule standardisation' to the nexus of peace-building and state-making, this paper seeks to advance existing debates on this delicate relationship.